Degenerative Changes in the Claustrum and Endopiriform Nucleus after Early-Life Status Epilepticus in Rats - Druga, Rastislav; Mares, Pavel; Salaj, Martin; Kubova, Hana (International journal of molecular sciences, 2024)
The aim of the present study was to analyze the location of degenerating neurons in the dorsal (insular) claustrum (DCL, VCL) and the dorsal, intermediate and ventral endopiriform nucleus (DEn, IEn, VEn) in rat pups following lithium-pilocarpine status epilepticus (SE) induced at postnatal days [P]12, 15, 18, 21 and 25. The presence of Fluoro-Jade B-positive neurons was evaluated at 4, 12, 24, 48 h and 1 week later. A small number of degenerated neurons was observed in the CL, as well as in the DEn at P12 and P15. The number of degenerated neurons was increased in the CL as well as in the DEn at P18 and above and was highest at longer survival intervals. The CL at P15 and 18 contained a small or moderate number of degenerated neurons mainly close to the medial and dorsal margins also designated as DCl ("shell") while isolated degenerated neurons were distributed in the VCl ("core"). In P21 and 25, a larger number of degenerated neurons occurred in both subdivisions of the dorsal claustrum. The majority of degenerated neurons in the endopiriform nucleus were found in the intermediate and caudal third of the DEn. A small number of degenerated neurons was dispersed in the whole extent of the DEn with prevalence to its medial margin. Our results indicate that degenerated neurons in the claustrum CL and endopiriform nucleus are distributed mainly in subdivisions originating from the ventral pallium; their distribution correlates with chemoarchitectonics of both nuclei and with their intrinsic and extrinsic connections.
Keywords: endopiriform nucleus; Claustrum; Rats; Neurons; Cerebral Cortex; neurodegeneration; ontogeny; neurony; krysa rodu Rattus; status epilepticus; Status Epilepticus; claustroamygdaloid complex; claustrum; Animals; zvířata; mozková kůra; klaustrum